The Impact of Social Media on Adolescent Mental Health: A Comprehensive Review - Talukdar, Jeuti (Integrated Journal for Research in Arts and Humanities, 2024)
Social media has become an integral part of adolescent life, with platforms like Instagram, Snapchat, and Facebook dominating their daily interactions. While social media offers numerous benefits, concerns about its impact on adolescent mental health have escalated. This research article provides a comprehensive review of existing literature to explore the complex relationship between social media use and adolescent mental health. It examines various factors such as cyberbullying, social comparison, fear of missing out (FOMO), and the effects of excessive screen time on psychological well-being. Additionally, it discusses potential protective factors and interventions to mitigate the negative impact of social media on adolescent mental health. By synthesizing current research findings, this article aims to provide insights for policymakers, educators, and parents to promote healthy social media use among adolescents.